Prospective, Randomized, Multicenter Trial of Peroneal Electrical Transcutaneous Neuromodulation vs Solifenacin in Treatment-naïve Patients With Overactive Bladder - Krhut, Jan; Rejchrt, Michal; Slovak, Martin; Dvorak, Roman V; Peter, Lukas; Blok, Bertil F M; Zvara, Peter (The Journal of urology, 2023)
PURPOSE: We investigated the safety and efficacy of peroneal electrical transcutaneous neuromodulation using the URIS neuromodulation system in a home-based setting in comparison with standard treatment using solifenacin in treatment-naïve female patients with overactive bladder. MATERIALS AND METHODS: A total of 120 patients were screened, of whom 77 were randomized in a 2:1 ratio to 12 weeks of treatment with daily peroneal electrical transcutaneous neuromodulation or solifenacin 5 mg. The primary endpoint was safety; efficacy assessments included proportion of responders, defined as subjects with ≥50% reduction in bladder diary-derived variables; Overactive Bladder-Validated 8-question Screener, and European Quality of Life-5 Dimensions questionnaire; and treatment satisfaction after 12 weeks of therapy. RESULTS: Seventy-one out of 77 randomized patients completed the study. In the peroneal electrical transcutaneous neuromodulation group 6/51 (12%) patients reported a treatment-related adverse event vs 12/25 (48%) in the solifenacin group (P < .001). No clinically significant changes were observed in any other safety endpoint. The proportions of responders in the peroneal electrical transcutaneous neuromodulation group vs the solifenacin group were 87% vs 74% with respect to Patient Perception of Intensity of Urgency Scale grade 3 urgency episodes, 87% vs 75% with respect to grade 3+4 urgency episodes, and 90% vs 94% with respect to urgency incontinence episodes. In post hoc analyses we observed significant improvement over time in multiple efficacy variables in both treatment arms. CONCLUSIONS: Peroneal electrical transcutaneous neuromodulation is a safe and effective method for overactive bladder treatment associated with a significantly lower incidence of treatment-related adverse events compared to solifenacin and a considerably better benefit-risk profile.
Keywords: solifenacin sukcinát; hyperaktivní močový měchýř; lower urinary tract symptoms; Humans; Solifenacin Succinate; Quality of Life; Female; výsledek terapie; lidé; urinary bladder; antagonisté muskarinových receptorů; kvalita života; solifenacin succinate; ženské pohlaví; Treatment Outcome; overactive; transcutaneous electric nerve stimulation; prospektivní studie; peroneal nerve; Muscarinic Antagonists; Urinary Bladder, Overactive; Prospective Studies